Gaya Penginjilan Kristen Progresif: Tantangan Bagi Usaha Penginjilan Kristen Konservatif - Ayub Sugiharto; Etni Grace Andi Yusuf (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
The phenomenon of progressive Christianity has become a serious concern within Indonesian Christianity because it introduces theological perspectives and evangelistic practices that differ from conservative Christian traditions, particularly regarding the exclusive understanding of salvation. This article formulates the following research questions: how is the evangelistic style of progressive Christianity developed, and why does it pose a challenge to conservative Christian evangelism? The urgency of this study lies in the church’s need to respond to shifts in evangelistic approaches that are increasingly contextual and socially oriented. This study employs a descriptive qualitative method through the analysis of theological literature. The findings indicate that progressive Christianity promotes a holistic model of evangelism that emphasizes relationships, dialogue, and social justice, with minimal emphasis on personal conversion. In conclusion, conservative Christian evangelism needs to formulate contextual strategies without obscuring the core message of the Gospel. This study recommends strengthening theological foundations while cultivating social sensitivity in evangelistic practice.